2023
DOI: 10.1007/s44246-023-00048-2
|View full text |Cite
|
Sign up to set email alerts
|

Size and composition of colloidal phosphorus across agricultural soils amended with biochar, manure and biogas slurry

Abstract: The long-term application of organic amendments like manure, biochar and biogas slurry can increase phosphorus (P) levels in agricultural soils; however, at present, it's not clear how this affects the P association with different mobile water-dispersible colloidal particles (Pcoll). Thus, this study aimed to assess the effects of the long-term application of different organic amendments on the abundance, size and compositional characteristics of Pcoll. For this purpose, a total of 12 soils amended with the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…In agricultural soil-plant systems an accurate quantification of Si contents in plant materials is crucial for assessing crops' need for Si supply and Si fertilization efficacy, because soil Si availability is often deduced from plant Si contents in agronomic studies (Korndörfer et al, 2001;Miles et al, 2014;Wu et al, 2020). In this context, a reliable, fast, and cost-effective method for the quantification of Si in soil amendments/fertilizers like, e.g., biochar or slags (Eltohamy et al, 2023;Haynes, 2017;Li et al, 2019) would be greatly appreciated by agricultural scientists as well as practitioners.…”
Section: Open Access Edited Bymentioning
confidence: 99%
“…In agricultural soil-plant systems an accurate quantification of Si contents in plant materials is crucial for assessing crops' need for Si supply and Si fertilization efficacy, because soil Si availability is often deduced from plant Si contents in agronomic studies (Korndörfer et al, 2001;Miles et al, 2014;Wu et al, 2020). In this context, a reliable, fast, and cost-effective method for the quantification of Si in soil amendments/fertilizers like, e.g., biochar or slags (Eltohamy et al, 2023;Haynes, 2017;Li et al, 2019) would be greatly appreciated by agricultural scientists as well as practitioners.…”
Section: Open Access Edited Bymentioning
confidence: 99%
“…This is primarily due to favored reductive dissolution reactions, in which iron (Fe) and manganese (Mn) oxides are solubilized, and P associated with them is released into the soil pore water. , Additionally, changes in soil pH resulting from flooding may further contribute to enhanced P release . Once P is released into soil pore water, colloidal particles, capable of settling yet remaining suspended for extended periods, transport this P to adjacent water bodies, , constituting a nonpoint source of pollution. , Recent studies have highlighted the association of elevated P concentrations in soil pore water, streams, and various aquatic environments with colloidal particles. Hence, understanding the behavior of colloidal P (P coll ) and associated components under anoxic conditions is critical for an accurate risk assessment of P loss in floodplain soils.…”
Section: Introductionmentioning
confidence: 99%
“…The P coll is recognized as a particularly mobile form of P, , contributing significantly to P loss from agricultural systems , and eutrophication of freshwater bodies. , It constitutes a substantial portion of total P in agricultural systems (13%–95%) , and streams (up to 30%). , Soil P coll mobility is influenced by various physical, chemical, and biological factors, , with pH, organic carbon (OC), and elements such as Fe, aluminum (Al), Mn, and calcium (Ca) being significant. , Despite its known importance, P coll behavior under reducing (anoxic) conditions is under-researched. A prior study on grassland soils revealed the anoxia-induced release of colloid- and nanoparticle-bound P < 450 nm, influenced by Fe .…”
Section: Introductionmentioning
confidence: 99%
“…The addition of biochar generally improves soil P availability. This improvement primarily stems from the dissolution of P from the biochar material, the increased reduction and dissolution of P in Fe(III) hydroxide, and mineralization of soil organic P by promoting the activities of microorganisms or phosphatase (Eltohamy et al 2023;Yang et al 2021;Zhou et al 2020). However, the conflicting results could potentially be caused by the immobilization of P through the adsorption or precipitation (Yang et al 2019;Chintala et al 2014) caused by an elevation in soil pH and crop uptake (Xu et al 2016).…”
Section: Introductionmentioning
confidence: 99%